THE EFFECT OF MODERN FAST-FOOD PRODUCTS ON THE ANATOMICAL CONDITION OF THE GASTROINTESTINAL MUCOSA - Mavluda Akbarova Nodirbek qizi; Tursunqulov Xushnudbek Mahmatqul o‘g‘li; Otajonova Aziza Karimjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In recent years, the consumption of fast-prepared food products, known as fast food, has significantly increased. These products contain high amounts of fats, salt, and various chemical additives that may have negative effects on the human body, especially on the gastrointestinal system. This article analyzes the impact of fast-food products on the anatomical condition of the gastrointestinal mucosa. According to the results of the study, regular consumption of such foods may lead to inflammation of the gastric mucosa, digestive disorders, and changes in intestinal microflora.